Fatigue life evaluation for notched single-crystal Ni-based superalloys considering inhomogeneous rafting microstructure. (January 2023) - Fan, Y.S.; Yang, X.G.; Tan, L.; Sui, T.X.; Shi, D.Q.; Liu, H.
Highlights: A framework for fatigue life prediction of notched single crystal Ni-based superalloys with inhomogeneous rafting is established. A novel strain energy density is proposed considering the effect of microstructural rafting on plastic and elastic parts. Deformation of degraded materials near the central hole is depicted by a microstructure-sensitive constitutive model. The uncertainty of predicted life induced by microstructure statistics is evaluated based on the distribution of the real microstructural features. Abstract: Hot-section components made by single crystal (SC) Ni-based superalloys with geometrical discontinuities such as film holes suffer from spatially inhomogeneous rafting of the γ'/γ microstructure due to harsh circumstances. Therefore, low cycle fatigue (LCF) life prediction is critical for ensuring the safety of engineering structures. Within this regard, an energy-based LCF life model is proposed based on the concept of the strain energy gradient by introducing the effect of rafting into the plastic and elastic parts of the strain energy density. The inhomogeneous microstructure degradation of a centre-hole specimen is depicted by stress-assisted rafting and stress-free isotropic coarsening, whereas the inelastic deformation behaviour of materials near the central hole is simulated by a microstructure-sensitive constitutive model. Combined with the concepts of modified strain energy density, effective damage zone and weight function, the proposed life model achieves a good prediction accuracy in ± 2 scatter bands against the experimental data of the centre-hole specimens with different rafting treatments. Finally, the uncertainty of the proposed life prediction model induced by the statistical dispersion of the microstructure is estimated. The results show that the uncertainty of the predicted lifetimes decreases with the rafting extent and fatigue life, even though the distribution of the γ channel width of the alloy with heavily rafting alloys is highly dispersed.